The Effect of Polymer Mixing Time on the Strength of HPAM-Cr(III) Gels - Iskander Gussenov (Eurasian Chemico-Technological Journal, 2023)
The dissolution of hydrolyzed polyacrylamide, commonly used in gel treatments for enhanced oil recovery, takes between 2‒3 to over 24 h at 20‒25 °C. The duration is influenced by factors such as polymer molecular weight and brine salinity. In injection/production wells, gel treatments often involve injecting 50‒150 m3 of polymer solution within 1‒2 days, resulting in the injection of partially dissolved polymer. This raises concerns about the stability and strength of gels containing partially dissolved polymer particles. This study demonstrates that when undissolved polymer particles are kept suspended during the gelation process, there is no significant visual distinction between gels obtained from